Analisis Kesulitan Belajar Matematika Dalam Menyelesaikan Soal Pilihan Ganda Konteks Sehari-hari Materi Perkalian Pada Peserta Didik Kelas IV Sekolah Dasar Negeri 24 Pontianak Tenggara - Makarius Iman Kalis; Hairida Hairida; Rio Pranata (Mathematics Education Study Program, 2025)
The aim of this study is to determine whether there are still students experiencing learning difficulties in solving multiplication word problems within the learning process of the Merdeka Curriculum. This research uses a Descriptive Quantitative method. The data sources for this study are 22 fourth-grade students from State Elementary School 24 Pontianak Tenggara and one class teacher. The data collection instruments used in this research are observation, interviews, and test questions. The results of the study indicate that 8 out of the 22 fourth-grade students did not meet the school's minimum mastery criteria of 75. A total of 8 students (36%) still experience learning difficulties in solving multiplication word problems.